Degradação de fármacos em efluente de uma estação de tratamento de esgoto sanitário utilizando processos avançados - Bisognin, Ramiro Pereira (2018)
The high worldwide consumption of remedies, coupled with the incomplete assimilation by animals and humans and the deficient removal by conventional effluent treatment systems, made the pharmaceuticals a persistent group of micropollutants. For this reason, the main goal of this thesis was to study the degradation and/or simultaneous removal of pharmaceuticals in a wastewater treatment plant (WWTP) by biological processes and by advanced oxidation using ozone, ultraviolet radiation and combinations with peroxide hydrogen. The study was carried out in three stages, the first one consisted in the investigation of the occurrence, fate and removal of 43 pharmaceuticals and hormones in effluent and sludge of the largest WWTP in Rio Grande do Sul (Southem Brazil), in the months of November 2017, March and April 2018. The determination of the pharmaceuticals was performed by a ultra high-performance liquid chromatography coupled to mass-mass spectrometry (UHPLC-MS/MS). Thus, 13 pharmaceuticals were detected in the crude effluent and 11 in the treated one. Although the highest concentrations in the raw effluent were paracetamol (137.98 μg L-1) and caffeine (35.29 μg L- 1), the highest diversity was of antibiotics at concentrations ranging from 0.023 to 1.374 μg L-1, for metronidazole and sulfamethoxazole, respectively. The pharmaceuticals doxycycline, fembendazole, norfloxacin and tetracycline were detected only in the sludge, but the highest concentration was ciprofloxacin (5.034 mg kg-1). During the treatment, increases in the concentration of some pharmaceuticals were recorded, as well as removals above 97%. However, high pharmaceutical loads (511.466 g d-1) were observed in the recipient water body. The second step consisted of the degradation of the 11 pharmaceuticals detected in the WWTP, using O3 in two dosages (0.5 and 0.9 mgO3 mgCOD-1), UV photolysis (254 nm), and the O3/UV, H2O2/UV and O3/H2O2/UV with 0.5 mgO3 mgCOD-1 and 25 mgH2O2 L-1. For degradation assays, the active ingredients ciprofloxacin, oxytetracycline, paracetamol, sulfamethoxazole and trimethoprim had increased concentrations above the predicted no effect concentration (PNEC). The study were performed at a ambient temperature of 20.60 ± 0.30 ºC and pH 6.94 ± 0.02, with aliquots being sampled at 7.5 and 15 min. The O3/H2O2/UV process was more efficient for the degradation of all detected pharmaceuticals, allowing a reduction of 89.32% of oxytetracycline, 96.79% of caffeine, 97.40% of trimethoprim, 97.75% of ciprofloxacin, 99.79% sulfamethoxazole, 99.96% paracetamol and 100% of clindamycin, ofloxacin, sulfadiazine, sulfathiazole and tylosin. The same process was responsible for the highest percentage of mineralization (60.52%), proving the synergetic effect between the combined oxidizing agents. Finally, the third step consisted in evaluating the (eco)toxicity of the three groups of effluents: (a) treated by biological processes, (b) with increased concentration of pharmaceuticals, and (c) posttreated by O3/H2O2/UV. The levels of thiobarbituric acid reactive substances (TBARS) and the activity of the enzymes acetylcholinesterase (AChE), catalase (CAT) and glutathione-S-transferase (GST) were evaluated in different organs of fish of the species Astyanax bimaculatus exposed to effluents for 14 days. Thus, it was evidenced that residuals of pharmaceuticals can cause oxidative stress, affecting biochemical and enzymatic parameters in Astyanax sp., as well the O3/H2O2/UV process can reduce damages to fish even with the possible formation of metabolites, which have been shown be less toxic than the original compounds.